2008
DOI: 10.1021/jo800473x
|View full text |Cite
|
Sign up to set email alerts
|

Photoaddition Reactions of 1,2-Diketones with Silyl Ketene Acetals. Formation of β-Hydroxy-γ-ketoesters

Abstract: Photochemical reactions taking place between 1,2-diketones and silyl ketene acetals and their excited state reaction mechanisms have been explored. Irradiation of benzene, acetone, or acetonitrile solutions containing 1,2-diketones and silyl ketene acetals is observed to promote formation of 1,4-dioxenes, resulting from [4 + 2]-cycloaddition, oxetanes, arising by Paterno-Buchi processes, and beta-hydroxy-gamma-ketoesters, generated by SET-promoted Claisen-type condensation. These competitive pathways leading f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Second, solvent polarity is not significant factor that governs the reaction pathways, which are found in previous studies. 1,4,13 Even though more studies are necessary to investigate the substituent' s effect of silyl enol ether and reaction pathways in detail about the photoreaction of 1,2-diketones and silyl enol ethers, observations made in this study show that SET promoted pathways take place highly efficiently and regioselectively.…”
Section: Methodsmentioning
confidence: 70%
See 1 more Smart Citation
“…Second, solvent polarity is not significant factor that governs the reaction pathways, which are found in previous studies. 1,4,13 Even though more studies are necessary to investigate the substituent' s effect of silyl enol ether and reaction pathways in detail about the photoreaction of 1,2-diketones and silyl enol ethers, observations made in this study show that SET promoted pathways take place highly efficiently and regioselectively.…”
Section: Methodsmentioning
confidence: 70%
“…In recent studies, we explored photochemical reactions of 1,2-diketone and silyl ketene acetals and showed that versatile C-C or C-O bond forming processes take place. On the basis of an analysis of the protoproducts presented previous study 1 , ground state/ excited state redox properties of 1,2-diketone electron acceptor [2][3] and silyl ketene acetal electron donor 4,5 , and results of photoreactions of monoketone analogs 4,[6][7][8] give plausible mechanistic pathways for 1,2-diketone with silyl ketene acetals (Scheme 1). Single electron transfer (SET)-promoted or direct [4+2] cycloaddition 1,9 , classical Paterno-Buchi [2+2] cycloaddition 1,4,10 , and sequential SET-desilylation processescompete for deactivation of the 1,2-dicarbonyl excited state by the silyl ketene acetals.…”
mentioning
confidence: 99%
“…While phenanthrenequinone preferentially adds with both carbonyl oxygens to give the [4 + 2] cycloadduct, acenaphthenequinone reacted with only one carbonyl group to exclusively yield the [2 + 2] addition product [64]. In the photoreactions of acenaphthenequinone with silyl ketene acetals in benzene, the [4 + 2] photocycloadducts could be obtained with modest yield [78].…”
Section: Photo-induced Cycloaddition Reactions Of α-Diketonesmentioning
confidence: 99%
“…Photocycloadditions of acyclic o -diones including biacetyl, benzil and 1,2-diketones conjugated with ene-yne have been reported. The photocycloaddition of biacetyl with olefins such as indene, furan, and enol ether gave oxetanes with higher orientational selectivity than in the case of monoketones [78,79]. The photoreaction of biacetyl with electron-deficient olefins did not give cycloadducts, indicating that the excited biacetyl was electrophilic in its reaction with olefins.…”
Section: Photo-induced Cycloaddition Reactions Of α-Diketonesmentioning
confidence: 99%
See 1 more Smart Citation